Cytotoxicity and Antibacterial Activity of Mineral Trioxide Aggregate Cement with Radiopacity Introduced by ZrO2 - Lidia Ciołek; Zbigniew Jaegermann; Ewa Zaczyńska; Anna Czarny; Monika Biernat; Arkadiusz Gąsiński; Agnieszka Jastrzębska; Michał Gloc; Andrzej Olszyna (Bioinorganic Chemistry and Applications)
The article presents the results of in vitro studies on cytotoxicity and antibacterial activity of new MTA-type cements, developed on the basis of the sintered tricalcium silicate enriched with ZnO, along with an agent introducing the radiopacity in the form of ZrO2. The new materials have been developed to ensure that their physical and chemical properties are suited for endodontic applications. The cements were evaluated via characterisation of setting time, compressive strength, as well as translucency on X-ray images, and bioactivity in the simulated body fluid (SBF). The μCT was used to test the influence of the ZrO2 grains in the powder component on the microstructure of the produced cement. Then, the cytotoxic action of the cements was evaluated by applying a reference L-929 cell line. The conditions of the culture upon contact with the tested materials or with extracts from the cements were assessed using image analysis or an MTT colorimetric assay. Two strains of streptococci, Streptococcus mutans and Streptococcus sanguinis, were used to study the antibacterial activity of the tested cements with ZrO2 acting as the agent introducing the radiopacity. The new cements are characterised by appropriate properties as far as retrograde root canal filling is concerned.